Awareness on impacts of globalization and ICT among women in Malaysia. - Salleh, Naimah; Othman, Mumtazah; Yahaya, Nurizan; Hashim, Aziah; Sabri, Bukryman (2008)
Malaysia aspires to become a developed and industrializes country by the year 2020 that thrives on national unity, racial harmony, economic aspiration and social prosperity. The strategies to be undertaken are called Vision 2020. Since the launching of Vision 2020 in 1991, concerted efforts has been undertaken to progress Malaysia towards a knowledge based economy with ICT (Information and Communication Technology) facilitating the development. ICT is one of the driving forces of globalization. While ICT can provide opportunities for development, there are inequalities among users in the access of ICT because of locality, income and language barrier. In Malaysia, personal computer used locally increased from 0.84% (1990) to 12.6% (2001). The objective of this study was to examine Malaysian consumer awareness on some basics issues related to globalization and ICT. The difference in level of consumer’s awareness among selected variables (age, level of education and level of income) were also examined. The study was conducted among 418 urban woman in Peninsular Malaysia. Respondents were randomly selected from among workers in public and privates sectors and entrepreneurs. The questionnaire consisted of two parts: (i) socio-demographic background and (ii) consumer awareness regarding globalization and ICT. The awareness is measured based on level of agreement of nine statements on basic issues of globalizations and ICT. A total of 418 women were involved in this study. Average age was 40 years old and 94.5 % were married. In terms of educational status, 45.5 % were found to have completed high school, 22 % were university graduates and 18 % have diploma/ Certificate. Average household income was RM 2030.00 (US 580.00) which represented lower middle income households. The mean scores value implied that respondents were aware on some issues related to globalization and ICT. Frequency distribution of each statement indicated that 90.4% of respondents were very aware that globalization will create a borderless world and 79.7% believed that globalization will affect them. Majority of respondents (83.1%) are competent in using the computer and 82.5% are able to control the negative impacts of internet. Furthermore, 84.3% of respondents agreed that the Malaysian future generations will find it easier to be employed by the multinational company. However the respondents did not agreeable on some issues. Almost half (50.4%) agreed that trade agreements such as AFTA and WTO have negative impacts on Malaysian economy. Forty seven percents agreed that internet has negative impact and as many as 84.1% of respondents believed that society might not be able to control the effect of information overload. A much as 41.4 % of respondents were not able to utilize the information from ICT due to inability in understanding the English language. The outcome of the ANOVA indicated that there were no significant differences in mean scores for most of the statements due to differences in age except for statement on competent in using computer (F3, 407 =3.37, p ≤ 0.05). However, there were significant differences among the educational levels in most issues related to globalization and ICT. Respondents with higher educational level were more aware of the impact of the globalization on themselves (F2, 402 = 4.28, p ≤ 0.05) and globalization will result in a borderless world (F2, 407 = 5.14, p ≤ 0.01). The study implied that education and competency in English language is crucial for society to be more prepared in facing the challenges of globalization and ICT era. The society also needs to be better empowered to control the negative impacts of ICT for them to progress positively. Malaysia should continue promoting an enabling environment for the consumer through appropriate policies on education in e-learning, k-economy and language enrichment in order to reduce the digital divide.